Late presentation for human immunodeficiency virus HIV diagnosis results of a Belgian single centre. Issue 1 (February 2013) - Yombi, J. C.; Jonckheere, S.; Vincent, A.; Wilmes, D.; Vandercam, B.; Belkhir, L.
Abstract : Background Antiretroviral therapy reduces mortality and morbidity in HIVinfected individuals, most markedly when initiated early, before advanced immunodeficiency has developed. Although the international guidelines recommend starting antiretroviral therapy ART with a high CD4 cell count level, in the practice, this is particularly challenging to achieve, especially in late presentation of HIV diagnosis. The aim of this study was to determine the frequency and the demographic features associated with late presentation for HIV diagnosis in our Centre. Methods All newly diagnosed patients with HIV between January 2007 and December 2011 in our AIDS Reference Centre, were included. Late presenter patient was defined as patient with CD4 count 350mm 3 at the time of diagnosis. Demographic age, sex, ethnicity, migration and clinical characteristics transmission mode, CD4 cell count, viral load were collected. We also collected data on outcome median day of hospitalization, mortality, virological response to ART and lost to followup LTFU. LTFU was defined as patient without any medical contact and viral load measurements during two consecutive years in our centre. Results From 2007 to 2011, 154 429 out of 359 patients newly diagnosed with HIV were late presenters. According to univariate analysis, age 50, female gender, migrant from subSaharan Africa and heterosexual contact were associated with late presentation for HIV diagnosis. In the multivariate analysis, age 50, heterosexual contact and migrant status particularly women were the only independent risk factors for late presentation. Late presenters tend to have a worse outcome than nonlate presenters. Conclusion A considerable proportion of patients continue to be diagnosed with advanced HIV disease, despite the fact that risk factors for late presentation have been clearly identified. Despite high testing rate for HIV in Belgium, highrisk population like migrant, heterosexual contact, remain under tested. In order to be able to detect and treat all patients with high CD4 cell count as recommended by all international guidelines, we recommend developing testing policies specifically focused on these categories at high risk for late presentation.